Human fluids alter DNA-acquisition in Acinetobacter baumannii - Martinez, Jasmine (2019)
Transformation is one of the mechanisms of acquisition of foreign genetic material leading to the emergence of multidrug resistant (MDR) bacteria. Recently, human serum albumin (HSA) was shown to specifically increase transformation frequency in the nosocomial pathogen Acinetobacter baumannii. To further assess the relevance of HSA as a possible modulator of A. baumannii transformation in host-pathogen interactions, in this work we examined the effect of different human fluids. We observed a significant increase in transformation frequencies in the presence of pleural fluid, whole blood cells and liquid ascites, and to a lesser extent with urine. The observed effects correlate with both HSA and bacterial content found in the assayed patient fluids. Taken together, these results are in agreement with our previous findings that highlight HSA as a possible host signal with the ability to trigger natural transformation in A. baumannii.